The attitudes of owners and veterinary professionals in the United Kingdom to the risk of adverse events associated with using non- steroidal anti-inflammatory drugs (NSAIDs) to treat dogs with osteoarthritis - Belshaw, Zoe; Asher, Lucy; Dean, Rachel S. (Elsevier, 2016)
Non-steroidal anti-inflammatory drugs (NSAIDs) are commonly prescribed by veterinary surgeons for the treatment of canine osteoarthritis, and affected dogs may receive these drugs for long periods of time. Whilst short term administration of NSAIDs to dogs is linked to adverse events such as gastrointestinal haemorrhage and renal injury, reports of adverse events associated with their long-term administration are limited in the veterinary literature. This study aimed to investigate the attitudes towards the long term use of NSAIDs for canine osteoarthritis held by three groups who manage osteoarthritic dogs in the United Kingdom: dog owners, veterinary surgeons and veterinary nurses. A qualitative methodology was adopted, using semi-structured interviews and focus groups. Thematic analysis of these data identified three themes: awareness of potential risks; recognition of adverse events; and influence of risk perception on the use of NSAIDs. Awareness of, and concern about, the risk of adverse events associated with NSAID administration to dogs with osteoarthritis was high in all groups, with veterinary surgeons being one of a variety of information sources used by owners to acquire this knowledge. Veterinary surgeons described difficulty in recognising, managing and avoiding adverse events associated with NSAIDs. When adverse events occurred, a wide range of management approaches were adopted ranging from a brief drug respite to permanent cessation of administration of any NSAIDs to that dog. Commonly employed approaches to minimise risk included dose reduction and screening blood tests. This study describes a high level of concern about the risks associated with long term NSAID administration to dogs with osteoarthritis and highlights a diverse range of strategies employed to minimise these risks. The evidence base for these strategies is poor, and this may present a risk to animal welfare if the affected dogs are not receiving adequate analgesia. In order to address this, more accurate and comprehensive data must be supplied to both veterinary professionals and owners on the true frequency of adverse events associated with long term administration of veterinary NSAIDs and how best to avoid them.